Uracil influences quorum sensing and biofilm formation in Pseudomonas aeruginosa and fluorouracil is an antagonist - Ueda, Akihiro (Blackwell Publishing Ltd, 2009)
Pseudomonas aeruginosa is an ubiquitous, opportunistic pathogen whose biofilms are notoriously difficult to control. Here we discover uracil influences all three known quorum‐sensing (QS) pathways of P. aeruginosa. By screening 5850 transposon mutants for altered biofilm formation, we identified seven uracil‐related mutations that abolished biofilm formation. Whole‐transcriptome studies showed the uracil mutations (e.g. pyrF that catalyses the last step in uridine monophosphate synthesis) alter the regulation of all three QS pathways [LasR‐, RhlR‐ and 2‐heptyl‐3‐hydroxy‐4‐quinolone (PQS)‐related regulons]; addition of extracellular uracil restored global wild‐type regulation. Phenotypic studies confirmed uracil influences the LasR (elastase), RhlR (pyocyanin, rhamnolipids), PQS and swarming regulons. Our results also demonstrate uracil influences virulence (the pyrF mutant was less virulent to barley). Additionally, we found an anticancer uracil analogue, 5‐fluorouracil, that repressed biofilm formation, abolished QS phenotypes and reduced virulence. Hence, we have identified a central regulator of an important pathogen and a potential novel class of efficacious drugs for controlling cellular behaviour (e.g. biofilm formation and virulence).